A systematic literature review on total quality management critical success factors and the identification of new avenues of research. Issue 1 (9th January 2017) - Aquilani, Barbara; Silvestri, Cecilia; Ruggieri, Alessandro; Gatti, Corrado
Abstract : Purpose: The purpose of this paper is to present a systematic literature review to identify new avenues of research in line with the ongoing changes in quality and management required to firms, especially regarding customers. Design/methodology/approach: This study uses a systematic review of the literature contained in the three databases Ebsco, JSTOR, and Springerlink and on the search engine Google Scholar. Findings: An analysis of the literature identifies three different clusters of papers: "identification" papers, which show that customer focus has gained importance in recent times; "implementation" papers, which highlight that a general or shared model or scale to successfully implement total quality management (TQM) does not yet exist; and "impact-on-performance" papers, which show that few studies have considered the relationship between TQM and the issues of both marketing and performance, underlining the most significant gap in the TQM literature. Research limitations/implications: This study is limited by the small number of databases and search engines used and by the restricted number of keywords used in searching these sources. Practical implications: This work highlights a gap in the existing research and thus an incomplete consideration of the interplay between management, marketing, and quality issues, all centered on customers and other stakeholders. Researchers and firms are thus advised to adopt a wider view that considers the role of the quality process to support the firm's engagement of customers in activities that enhance both the customer role and customer satisfaction. Originality/value: This study uses a systematic literature review to review all critical factors of TQM and identifies new research avenues and different approaches to implementing TQM, focusing on the central role that customers play in achieving firm success.